Pola, Makna, Serta Fungsi Pengaplikasian Slang Pada Kalangan Remaja Di Kabupaten/Kota Bandung - Firdausy, Rizky; Sulistyowati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Slang is one of the variations of social language that grows among people. Using slang in informal situations for adolescents serves as self-familiarity with other individuals. This research investigates the patterns, meaning, and functions of Sundanese slang in Bandung City/Regency. This research method uses a mix methods of qualitative and quantitative. The researcher collected the data through questionnaires via Google Forms with specific participant criterias to gain appropriate results. Twenty participants were selected based on age, birth, domicile in Bandung City/Regency, and Sundanese as their native language. In analysing the data, the researcher used O'Grady's (1996) theory regarding the word formation process. The results of this study indicate that the word formation processes of Sundanese slang is formed through the types of onomatopoeia (2.81%), derivation (4.22%), multiple processes, (7%) clipping, (8,45%), coinage (22.5%), acronym (24.6%), and blending (30.3%). In addition, slang functions were found into seven types, for humor, mockery, praise, brevity and concreteness, confidentiality, intimacy, and as an identity and group differentiator.